Beta-secretase-1 antisense RNA is associated with vascular ageing and atherosclerotic cardiovascular disease: atherosclerosis and ischaemic disease - Bampatsias, Dimitrios; Mavroeidis, Ioannis; Tual-Chalot, Simon; Vlachogiannis, Nikolaos I.; Bonini, Francesca; Sachse, Marco; Mavraganis, Georgios; Mareti, Alexia; Kritsioti, Chrysoula; Laina, Ageliki; Delialis, Dimitrios; Ciliberti, Giorgia; et al. (Thrombosis and haemostasis, 2022)
Background: The noncoding antisense transcript for β-secretase-1 (BACE1-AS) is a long noncoding RNA with a pivotal role in the regulation of amyloid-β (Aβ). We aimed to explore the clinical value of BACE1-AS expression in atherosclerotic cardiovascular disease (ASCVD).Methods: Expression of BACE1-AS and its target, β-secretase 1 (BACE1) mRNA, was measured in peripheral blood mononuclear cells derived from 434 individuals (259 without established ASCVD [non-CVD], 90 with stable coronary artery disease [CAD], and 85 with acute coronary syndrome). Intima-media thickness and atheromatous plaques evaluated by ultrasonography, as well as arterial wave reflections and pulse wave velocity, were measured as markers of subclinical ASCVD. Patients were followed for a median of 52 months for major adverse cardiovascular events (MACE). Results: In the cross-sectional arm, BACE1-AS expression correlated with BACE1 expression (r = 0.396, p < 0.001) and marginally with Aβ1-40 levels in plasma (r = 0.141, p = 0.008). Higher ACE1-AS was associated with higher estimated CVD risk assessed by HeartScore for non-CVD subjects and by European Society of Cardiology clinical criteria for the total population (p < 0.05 for both). BACE1-AS was associated with higher prevalence of CAD (odds ratio [OR] = 1.85, 95% confidence interval [CI]: 1.37-2.5), multivessel CAD (OR = 1.36, 95% CI: 1.06-1.75), and with higher number of diseased vascular beds (OR = 1.31, 95% CI: 1.07-1.61, for multiple diseased vascular beds) after multivariable adjustment for traditional cardiovascular risk factors. In the prospective arm, BACE1-AS was an independent predictor of MACE in high cardiovascular risk patients (adjusted hazard ratio = 1.86 per ascending tertile, 95% CI: 1.011-3.43, p = 0.046). Conclusion: BACE1-AS is associated with the incidence and severity of ASCVD.